Madeline's rescue - Bemelmans, Ludwig, 1898-1962 (Viking Press, 1953)
Madeline falls into the river Seine and nearly drowns, a courageous canine comes to her rescue. Now Genevieve the dog is Madeline's cherished pet, and the envy of all the other girls. What can be done when there's just not enough hound to go around?